STUDI TENTANG BUDAYA SEKOLAH DI SMA NEGERI 6 SIDRAP - Suardi Zain; Suhartini Khalik, Nuraini Kasman, Nadirah, Nurmayanti (CV. ADIBA ASIHA AMIRA, 2023)
This research comprehensively delineates the school culture at SMA Negeri 6 Sidrap, focusing on the school's vision and mission, physical and non-physical environment, facilities, the condition of teachers and students, and an introduction to the learning process. The school's vision emphasizes achievement, faith, culture, character, broad insights, and environmental awareness. Its mission includes active, creative, and innovative learning, the practice of religious teachings, and participation in environmental preservation. SMA Negeri 6 Sidrap boasts facilities encompassing classrooms, a library, computer laboratories, guidance and counseling rooms (BK), as well as other facilities such as the health unit (UKS), cooperative, student council room (OSIS), and administrative room (TU). The library's quality is marked by an adequate book collection, with ongoing efforts to enhance it. The computer laboratories are well- equipped, including WiFi and air conditioning. The condition of teachers at SMA Negeri 6 Sidrap includes the number of permanent teachers, honorary teachers, and administrative staff. Ratios of teachers to students and administrative staff to students are also outlined. Student admissions are conducted through zoning, achievements, and affirmative action. Observations in English, Indonesian language, and Infomatics classes reveal diverse teaching strategies, the use of technology, and positive interactions between teachers and students. Teachers are active in creating a conducive learning environment and providing appropriate feedback. This research also depicts activities inside and outside the classroom, patterns of student behavior, teaching and learning interactions, classroom management, as well as the role and activities of Guidance and Counseling (BK) in assisting students. This study presents a comprehensive overview of the school culture at SMA Negeri 6 Sidrap, providing valuable insights for the development of education in similar schools.